THE EFFECT OF FORENSIC ACCOUNTING ON FRAUD CONTROL IN PUBLIC SECTOR MINISTRIES IN RIVERS STATE - Dr. Solomon Egbe (American Journals Publishing, 2023)
The performances of government ministries are generally poor due to absence of an effectively functioning internal control system, high incidence of fraud and lack of accountability. Public sector fraud to a large extent has eaten deep into the blood stream of the Nigeria public sector which is the problem facing today’s Nigeria economy. The adoption of a democratic system of governance in the public sector has triple the epidemics of fraud in the public sector as politicians believe that public sector corruption is considered normal. Ministries, department and agencies fraud is considered a national problem that has eaten deep into the nation and has threatened the financial viability of the Nigeria economy. There is therefore an urgent need to install adequate fraud control technique in the Nigeria public- sector system to curb the menace of corruption and serve as a check mechanism to curb the ever changing and improving tactics of fraudster in government MDA’s. The research examined the relationship in existence between forensic accounting and fraud, control in some public sector ministries in Rivers State. The study adopted the descriptive survey method with sample size of 292, selected using taro Yamane formula from a total population of1,091 of the six ministries. 292 copies of questionnaires were administered among staff of the selected ministries. The statistical tool employed to examine the effect of the predator variables investigative accounting and litigation support services on fraud control is ordinary least square regression technique. Data obtained from the administered questionnaires was imputed into SPSS 20 for analysis.
Keywords: Investigative accounting. Internal control. Fraud Policy. Rivers State. Nigeria.